2016
DOI: 10.1186/s12939-016-0306-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessing equity in benefit distribution of government health subsidy in 2012 across East China: benefit incidence analysis

Abstract: BackgroundImproving the equitable benefit distribution of government health subsidies, particularly among the country’s poorer socioeconomic groups, is a major goal of China’s healthcare sector reform.MethodsBenefit incidence analysis was employed to measure the distribution of government health subsidies by income quintile. The concentration index (CI) of different levels of health care facility in urban and rural areas was calculated. A household survey complete through multistage stratified sampling was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
26
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
4
26
1
Order By: Relevance
“…For township health centers, deductibles were even removed, and reimbursement rates were raised to 90% or 100%. Numerous findings show that the poor were more likely to seek treatment in primary-level health-care facilities [ 48 ]. This design has lowered the threshold and economic burden for seeking treatment for enrollees with low economic background, thus benefitting the poor who need healthcare services from the medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…For township health centers, deductibles were even removed, and reimbursement rates were raised to 90% or 100%. Numerous findings show that the poor were more likely to seek treatment in primary-level health-care facilities [ 48 ]. This design has lowered the threshold and economic burden for seeking treatment for enrollees with low economic background, thus benefitting the poor who need healthcare services from the medical insurance.…”
Section: Discussionmentioning
confidence: 99%
“…However, ideal health outcomes are directly dependent on the distribution of the health workforces ( 6 ), and evidence shows there are tight relationships between number and quality of health workforces and primary health care services, vaccination coverage and maternal mortality rate ( 7 , 8 ). Often, there are many inequalities in the distribution of healthcare personnel within countries and between regions and provinces of a country ( 9 11 ). It is a considerable problem in developing countries that health-related workforce is condensed in big towns and cities, and rural regions are allocated only 23% and 38% of the country’s general practitioners and nurses, and these inequities resist against the changes ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the results in our study showed almost no differences between two groups in the rural areas. This implied that the implementation of NEMPs may have been obstructed in rural areas, when several studies attributed the obstruction to the deficiency [ 40 ] and inequity [ 41 43 ] of financial subsidies. Also, Table 2 shows the financial subsidies did not change after the introduction of NEMPs in the rural areas, resulting in the amount ratio and the income ratio of EMs did not change (Table 4 ).…”
Section: Discussionmentioning
confidence: 99%